Development Strategy of Key Basic Technologies for Marine Equipment to Enhance the Marine Strength of China - Peng Cai; Cungen Liu; Zhongqin Lin; Mingjian Lu; Qiang Fu; Sheng Dong; Xuguang Zhang; Shuguang Liu; Ni Feng; Shuhan Yang; Haixia Zhang (中国工程科学)
China's marine equipment application technologies have developed rapidly in recent years; however, basic technologies remain weak. Accelerating the breakthroughs of key basic technologies for marine equipment is crucial for enhancing the marine strength of China. This study analyzes the development demand of China for marine equipment, summarizes the essence of key basic technologies of marine equipment, and clarifies the global frontiers and development trends of marine equipment technologies from three aspects: marine transportation equipment, marine resource development equipment, and marine scientific research equipment. Moreover, it reviews the development status and major problems of China's marine equipment technologies, identifies ten key basic technologies that have a significant impact on the marine equipment industry, and outlines the development goals, roadmap, and key tasks of these key basic technologies. Safeguard measures are further proposed, including (1) emphasizing basic technology research for marine equipment to strengthen the top-level design for innovation, (2) advancing the construction of a multi-dimensional collaborative innovation system for the key basic technologies, and (3) promoting the globalization of China-led marine technologies and equipment.